2021
DOI: 10.1093/jtm/taab122
|View full text |Cite
|
Sign up to set email alerts
|

Prospective cohort study using ultrasonography of Schistosoma haematobium–infected migrants

Abstract: Background. Chronic infection with Schistosoma haematobium may lead to serious complications, including bladder carcinoma. Although it is recommended that only bladder masses not regressing within 6 months after praziquantel intake should be investigated invasively, cystoendoscopy is still often performed at diagnosis even in the absence of further signs of concern. No prospective study so far evaluated the evolution of bladder lesions after treatment in case of no risk of reinfection, which could inform case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
0
9
0
1
Order By: Relevance
“…It is also not yet clear how PZQ administration impacts chronic lesions (i.e. eggs-deposit induced fibrosis); according to some reports bladder lesions and fibrosis reverses after therapy, but advanced pathology may persist for a long time in spite of treatment or non-re-exposure [31,32]. A previous study in our area showed an improvement in clinical and analytical abnormalities following treatment of long-term resident migrants [13].…”
mentioning
confidence: 86%
“…It is also not yet clear how PZQ administration impacts chronic lesions (i.e. eggs-deposit induced fibrosis); according to some reports bladder lesions and fibrosis reverses after therapy, but advanced pathology may persist for a long time in spite of treatment or non-re-exposure [31,32]. A previous study in our area showed an improvement in clinical and analytical abnormalities following treatment of long-term resident migrants [13].…”
mentioning
confidence: 86%
“…The dynamic of bladder lesions after treatment suggests that the lesions usually begin to regress very quickly after PZQ treatment and, therefore, it is reasonable to perform cystoscopy with biopsy only in patients with signs (e.g., haematuria) or bladder lesion which persist > 6 months after treatment [ 109 , 110 ]…”
Section: Which Radiological Imaging Should Be Performed In Patients W...mentioning
confidence: 99%
“…Moreover, cystoscopy with biopsy is recommended in the evaluation of bladder lesions that have features suspected of malignancy and do not regress with antiparasitic therapy after 2–3 months and [ 83 , 109 , 110 ].…”
Section: Which Radiological Imaging Should Be Performed In Patients W...mentioning
confidence: 99%
“…Those infected are also usually found to suffer from advanced morbidity, indicating that management is often inappropriate in countries of origin, or screening implemented late upon arrival in Europe. For example, a survey [53] found that 47.6% of a group of immigrants to Italy aged 18-29 years infected with S. haematobium had bladder masses at ultrasound examination. Again from Italy, another survey [54] found that a high proportion of patients diagnosed with schistosomiasis, both asymptomatic and symptomatic, were screened or tested only several months after arrival in Italy and most of them presented with clinical apparent disease.…”
Section: Importation Of Cases Of Human Schistosomiasis Into Europementioning
confidence: 99%